2022
DOI: 10.1002/art.42051
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polygenic Risk Scores With Radiographic Progression in Patients With Rheumatoid Arthritis

Abstract: Objective To investigate whether polygenic risk scores obtained using data from a genome‐wide association study (GWAS) of rheumatoid arthritis (RA) susceptibility can be predictors of radiographic progression. Methods We constructed polygenic risk scores using GWAS summary data on associations of single‐nucleotide polymorphisms with RA susceptibility. The polygenic risk scores were stratified into quintiles based on levels of significance (ranging from top quintile of polygenic risk scores to bottom quintile).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Like the results of these studies, our results highlight a significant correlation of ACPA with MMP-9 level in synovial fluid, highlighting the greater importance of this serological parameter than RF for the rapid radiological progression of early RA. According to our results, multivariable risk assessment of rapid radiological progression of early RA showed that ACPA positivity with a polygenic risk score, as well as female gender and body mass index was associated with rapid progression of structural joint changes [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like the results of these studies, our results highlight a significant correlation of ACPA with MMP-9 level in synovial fluid, highlighting the greater importance of this serological parameter than RF for the rapid radiological progression of early RA. According to our results, multivariable risk assessment of rapid radiological progression of early RA showed that ACPA positivity with a polygenic risk score, as well as female gender and body mass index was associated with rapid progression of structural joint changes [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic risk scores for predicting clinical outcomes are also being investigated in the setting of rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). In RA, a polygenic risk score has recently been developed to predict severity of radiographic progression ( 13 ) and in SLE, a high genetic risk score was associated with organ damage and renal dysfunction ( 14 ).…”
Section: Role Of Genetics In Development Of Autoimmunitymentioning
confidence: 99%
“…In this paper from Tokyo (Japan) , a group of investigators has used data from a large genome-wide association study (GWAS) to create a PRS for rheumatoid arthritis, thereby assessing the potential associations and interactions of the various genetic factors associated with development of rheumatoid arthritis (RA). 3 The group used the model to predict the Sharp/van der Heijde score (SHS), indicating the nature and extent of disease progression. The model was initially developed in a training set of 500 cases, before testing it in a validation cohort of 740 cases.…”
Section: Polygenic Risk Scores Are Associated With Radiological Progr...mentioning
confidence: 99%
“…Essentially, this is a way to visualize additive and interacting genetic-related risk factors for a specific condition. In this paper from Tokyo (Japan), a group of investigators has used data from a large genomewide association study (GWAS) to create a PRS for rheumatoid arthritis, thereby assessing the potential associations and interactions of the various genetic factors associated with development of rheumatoid arthritis (RA) 3. The group used the model to predict the Sharp/ van der Heijde score (SHS), indicating the nature and extent of disease progression.…”
mentioning
confidence: 99%